Mechanisms of Formation and Realization of Political Potential of the Russian Youth: Problems and Integrative Conditions - Marina Sergeyevna Komarova (Управленческое консультирование)
Today the younger generation is in a stage of the formation and development of new sociopolitical roles. Transformations socio-political the practician complicates definition by young citizens of the of a social role and political positions that can’t but affect their political participation and behavior. Today most of experts come to opinion that youth send the activity to socio-political life of the Russian society - in policy, in elections, in local activity less and less. Thus that young people in the majority are interested today in life of society, they aren’t its active participants. They more likely only observers who perfectly understand requirements imposed to them by society, but don’t share those positions and the directions which are offered them today. In this connection the state and institutes of civil society will be always faced by tasks of the organization of effective transfer of experience to the younger generation, optimum inclusion of youth in social and political processes, creation of optimum conditions for self-realization of the young personality.